STRATEGI KOMUNIKASI IKATAN MAHASISWA MINANG (IMAMI) UNIVERSITAS RIAU DALAM MEMPERTAHANKAN EKSISTENSI KESENIAN RANDAI MINANGKABAU DI UNIVERSITAS RIAU - Safitri, Anita; Salam, Noor Efni (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
The Minangkabau randai art form is a cultural heritage that is currently experiencing decline due to westernization. Amidst the challenges of modernization, the Minangkabau Student Association (IMAMI) of Riau University strives to maintain the existence of randai art through a communication strategy by making IMAMI a forum for Minangkabau students to learn about Minangkabau culture. The purpose of this study is to examine how IMAMI's choice of communicators, audiences, and delivery media are used, and how reactions emerge to IMAMI's communication strategy. This study uses a descriptive qualitative approach. Informants were selected using purposive sampling, with a total of six informants, namely the chairperson of IMAMI, the head of the arts division of IMAMI, randai arts trainers and dancers, IMAMI alumni, and the general public (UNRI students). Data collection in this study was conducted through interviews, observation, and documentation. To ensure data validity, the researcher used source and method triangulation. The results of this study show that: 1) IMAMI selects communicators who understand randai art and participate in randai art performances so that they not only act as messengers, but also become representatives of Minangkabau culture. 2) Minang students at the University of Riau are the main target audience for introducing randai art. Determining this audience is important for the success of the communication strategy. 3) Informative, persuasive, and educational messages are used to attract the interest of students at the University of Riau. 4) Utilizing social media platforms such as Instagram and TikTok to disseminate information and communicate directly, for example by holding live performances. 5) The response generated by the audience through the enthusiasm of students for randai art, as well as the emergence of pride in Minangkabau culture. Keywords: Communication Strategy, IMAMI, Minangkabau Randai art